Understanding Mental Health through Self-Concept among Undergraduate Students - Ahmad, Anis; Kumari, Nidhi (Journal of Neonatal Surgery, 2025)
The self- concept has long been theorised as a determinant of psychological well-being. It is the organised set of beliefs and perceptions an individual holds about the self. The present study aimed to examine the relationship between self-concept and mental health among undergraduate students. This study was conducted with 360 undergraduate students (84 boys and 276 girls) using purposive sampling, aged 16 to 25 years. Self-concept was measured using Saraswat’s Self-Concept Questionnaire. It measures six dimensions of self-concept: Physical, Social, Temperamental, Educational, Moral, and Intellectual. Mental health was measured by the Mental Health Inventory developed by Jagdish and Srivastava. Data were analysed using the Pearson product-moment correlation and multiple linear regression. Results revealed that the overall self-concept score was not significantly related to overall mental health (r = .02, p > .05). However, Physical (r = .16) and Social (r = .13) dimensions of the self-concept were positively and significantly related to mental health. The Temperamental (r = -.32) and Intellectual (r = -.21) dimensions of self-concept, on the other hand, were negatively and significantly related to mental health. Multiple regression analysis stated that the six dimensions of self-concept jointly accounted for 23.9% of the variance in mental health scores. Physical, Social, Temperamental and Intellectual dimensions of self-concept emerged as significant individual predictors of mental health. The findings suggest that mental health is shaped by the specific facets of self-concept. Some dimensions, such as temperamental and intellectual self-appraisal, may operate in ways that run counter to common assumptions. Implications for student counselling and mental health promotion on campuses are discussed